Answer:
-1/2
Step-by-step explanation:
Answer:
m=9/8 or 1 1/8
Step-by-step explanation:
m= change in y over change in x
2 - -7 = 9
5 - -3 = 8
Answer:
(0,5)x3=(15,5)
Step-by-step explanation:
BDE are the correct options
Answer:
The function f(x) = -9.5 + 6 + x² is neither odd or even.
Step-by-step explanation:
We know that a function is termed as 'even' when
f(-x) = f(x) for all x
We know that a function is termed as 'odd' when
f(-x) = -f(x) for all x
Given the function
f(x) = -9.5x⁵ + 6 + x²
substitute x with -x
f(-x) = -9.5(-x)⁵ + 6 + (-x)²
as (-x)⁵ = -x⁵, so
f(-x) = -(-9.5x)⁵ + 6 + (-x)²
Apply exponent rule: (-a)ⁿ = aⁿ, if n is even
f(-x) = -(-9.5x)⁵ + 6 + x²
Apply rule: -(-a) = a
f(-x) = 9x⁵ + 6 + x²
As
f(-x) ≠ f(x) ≠ -f(x)
Therefore, the function f(x) = -9.5 + 6 + x² is neither odd or even.